Treatment utilization among people with drug use disorders in prison: a national longitudinal cohort study - Nicoline Toresen Lokdam; Marianne Riksheim Stavseth; Ingeborg Skjaervø; Anne Bukten (Health & Justice)
Abstract Background Drug use disorders are highly prevalent among people in prison. Nevertheless, treatment coverage for individuals with drug use disorders in prison remains understudied and unknown. The aim of this study was to estimate treatment coverage among a sample of people with harmful and likely drug dependence before entering prison and to investigate the factors associated with treatment utilization. Methods This was a longitudinal cohort study using baseline survey data linked to registry data on imprisonment and treatment utilization. The study is based on the Norwegian Offender Mental Health and Addiction (NorMA) cohort (n = 733) recruited in 2013–2014 from 57 Norwegian prisons. At baseline, participants reported drug use the year before imprisonment, using the Drug Use Disorder Identification Test (DUDIT). The outcome of interest was DUD treatment, defined as at least one DUD treatment episode from the specialized health services during baseline imprisonment. Results 40% of the sample had DUDIT scores that indicated likely drug dependence (≥ 25) and a need for treatment. Among this group, 64% received DUD treatment while imprisoned. Longer imprisonment (> 12 months; aOR = 8.87, p < 0.001), Nordic country of birth (aOR = 2.85, p = 0.003), daily/almost daily injecting drug use (aOR = 2.58, p < 0.001) and polydrug use (aOR = 2.19, p = 0.002) were positively associated with treatment utilization in prison. Conclusions Most people with likely drug dependence before entering prison in Norway received DUD treatment during their time in prison. More severe drug use (Injecting drug use and polydrug use), longer imprisonments and being born in the Nordics were positively associated with treatment utilization. People in prison must have access to adequate treatment during imprisonment, and further studies should investigate the possible individual or structural barriers resulting in treatment gaps, especially for people who are foreign born and people with short sentences.